Enforcement of the Crime of Money Laundering in Digital Financial Transactions - Ningtias, Ayu Dian; Sastradinata, Dhevi Nayasari; Isnaini, Enik; Suisno (Universitas Islam Lamongan, 2023)
Abstract These financial crimes can range from theft, fraud to taking advantage of other parties in the financial industry, for example: account theft, ATM browsing, credit card fraud, fake draws. Several cases of terrorist financing use digital payments as a means of online funding. There is also evidence that corrupt actors use digital payments to hide the proceeds of their crimes. This situation can certainly threaten economic stability and the integrity of the financial system. Therefore, a comprehensive regulatory framework through the establishment of.fintech legislation needs to be developed to maintain the integrity of digital payments and strengthen the government's regulatory function. Terrorist financing is even included in financial crimes: apart from hiding and protecting the origins of the proceeds of crime, it is also included in financial crimes in the money laundering group.